Receptiveness of American adults to COVID-19 vaccine boosters: A survey analysis - Stephen R. Neely; Joshua M. Scacco (Elsevier, 2022)
Objective: This Short Communication report summarizes results from a recent survey on the willingness of American adults to accept COVID-19 vaccine boosters. We seek to identify evolving hesitancies and objections to booster shots among those who previously accepted vaccination. Methods: A representative, web-based survey of 600 adults in the State of Florida was fielded, and the results are analyzed using both descriptive and inferential statistical methods. Results: The survey responses show that while booster shot hesitancy is relatively low among vaccinated Americans, nearly a third (30.4%) say that they are only somewhat likely or less to receive a vaccine booster shot. Statistical analysis shows that trust in public health guidance is the driving factor behind booster shot hesitancy, while significant differences also exist based on race and level of education. The most frequently cited objections to booster shots include concerns over the necessity of additional shots and adverse reactions to the initial vaccination. Conclusion: Objections to booster shots highlight emerging communications challenges that health professional will need to consider and address as vaccine guidance continues to evolve. Innovation: This study contributes to innovation in health communications by identifying emerging challenges and barriers in the ongoing effort to promote COVID-19 vaccination.